2015
DOI: 10.5152/tjg.2014.5064
|View full text |Cite
|
Sign up to set email alerts
|

Copper excess in liver HepG2 cells interferes with apoptosis and lipid metabolic signaling at the protein level

Abstract: Background/Aims: Copper is an essential trace element that serves as an important catalytic cofactor for cuproenzymes, carrying out major biological functions in growth and development. Although Wilson's disease (WD) is unquestionably caused by mutations in the ATP7B gene and subsequent copper overload, the precise role of copper in inducing pathological changes remains poorly understood. Materials and Methods: Our study aimed to explore, in HepG2 cells exposed to copper, the cell viability and apoptotic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Also, the accumulation of Cu oxide nanoparticles (CuO-NPs) in C6 glioma cells produces a severe loss in cell viability (assessed by MTT reduction and cellular lactate dehydrogenase activity) and cell membrane integrity (Joshi et al 2016). Similar results have been observed when Cu chloride was used (Nzengue et al 2012); also, HepG2 cell exposure to 10, 200, and 500 μM Cu sulfate for 8 or 24 h reduced the viability as compared with untreated cells (Liu et al 2014). In the present study, loss in cellular MTT reduction capacity was observed for all Cu conditions, suggesting that the MTT assay is a more sensitive indicator of Cu-induced cellular viability decrease than the TB-FDA assay.…”
Section: Discussionsupporting
confidence: 88%
“…Also, the accumulation of Cu oxide nanoparticles (CuO-NPs) in C6 glioma cells produces a severe loss in cell viability (assessed by MTT reduction and cellular lactate dehydrogenase activity) and cell membrane integrity (Joshi et al 2016). Similar results have been observed when Cu chloride was used (Nzengue et al 2012); also, HepG2 cell exposure to 10, 200, and 500 μM Cu sulfate for 8 or 24 h reduced the viability as compared with untreated cells (Liu et al 2014). In the present study, loss in cellular MTT reduction capacity was observed for all Cu conditions, suggesting that the MTT assay is a more sensitive indicator of Cu-induced cellular viability decrease than the TB-FDA assay.…”
Section: Discussionsupporting
confidence: 88%
“…A typical disadvantage of using nanoparticles is their rather high cytotoxicity. In particular, it was found that metal and metal-oxide nanoparticles, which had been implanted into mammalian cells, caused alteration of the normal function of mitochondria, an increase in the membrane permeability, and the generation of reactive oxygen species, which resulted in oxidative stress and cellular damage. , However, nanoparticles that are biocompatible and biodegradable (which strongly depends on their physical–chemical properties) can potentially be used for in vivo applications …”
Section: Introductionmentioning
confidence: 99%